Site Soil-Fertility and Light Availability Influence Plant-Soil Feedback - McCarthy-Neumann, Sarah; Kobe, Richard K. (Frontiers in Ecology and Evolution, 2019)
Negative plant-soil feedback (PSF) , where plant performance is reduced in soils conditioned by conspecifics, are widely documented in plant communities. However, the strength and sometimes direction of PSF can vary widely, presumably due to environmental context. We hypothesized that soil fertility and light availability influence the direction and strength of plant-soil feedback experienced by tree seedlings. We conducted a 10-week greenhouse experiment and assessed survivorship of black cherry (Prunus serotina) in low (~1% full sun) vs. high (~18% full sun) light availability and in non-sterile vs. sterile soils collected under the canopy of conspecific vs. heterospecific adult trees at five sites that vary in nutrient availability in Manistee National Forest, Michigan, USA. Northern red oak (Quercus rubra) also was included in the experiment, but no seedlings died and thus there are no survivorship responses to report. Prunus serotina seedlings experienced microbe-mediated negative plant-soil feedback in low fertility sites (higher C:N ratios and lower NH4+) but positive feedback at high fertility sites, but these feedbacks occurred only under high light availability. Consistent with these results, microbe-mediated negative PSF increased with soil Fe3+ and C:N ratios and decreased with NH4+. Thus lower fertility soils, characterized by high C:N and Fe3+availability and low NH4+, are associated with stronger negative conspecific feedback for P. serotina seedlings. Conversely, higher fertility soils flip the feedback to positive. Our results demonstrate the important role of environmental context, specifically light and soil nutrient availability, on the magnitude and direction of conspecific plant soil feedback. Thus, PSF is likely an important driver in plant community dynamics that may be either destabilizing (promote species coexistence) or stabilizing (promote monodominance) depending upon environmental context.